103 Computer assisted diagnosis and monitoring of Parkinson's disease. Issue 3 (9th February 2012) - Alty, J; Jamieson, S; Smith, S
Abstract : Background: Parkinson's disease (PD) can be difficult to diagnose and objectively monitor. A computer-based test would provide objective evidence to inform clinical diagnosis and monitor response to medication. This would have potential benefits for patients, clinicians, NHS budgets and the pharmaceutical industry. Methods: A proof of concept study was undertaken to evaluate a novel test for PD using electromagnetic tracking sensors in combination with custom written computer evolutionary algorithms. Each subject completed a line drawing of a pentagon and a finger tapping test to provide objective assessment of tremor and bradykinesia. Results: 50 PD patients and 38 controls were assessed after obtaining ethical approval and informed written consent. The system provided a diagnostic accuracy of 84.7%, despite the patients receiving medication to treat their symptoms. Conclusions: This technology is able to provide an objective assessment of movement disorders specific to Parkinson's disease which has the potential to assist in the reliable diagnosis of PD and be useful in evaluating new drugs and treatments.